Censors and society: the Roman censorship, 443 - 21 BC - Welbourn, Michael (2018)
The censorship was one of the Roman Republic's most significant magistracies. The range and importance of their duties – the census, the lectio senatus and recognitio equitum, letting public contracts and initiating public works, and the ceremony of the lustrum – meant that the office had a profound impact on Roman society. There is much modern scholarship on the censorship. But some of the arguments and conclusions put forward by earlier scholars, while valuable, need to be updated and certain misconceptions corrected. In particular, what is required is a greater focus on placing the censorship in its political and social context, into the political culture of the Roman Republic, in order to properly analyse the office, its wider function(s), and its influence on Roman society. At the same time, a careful consideration of what precisely the censors' duties involved and how each pair of censors carried these out is necessary. The present work hopes to address both aspects of this important magistracy.